Biologia floral e mecanismo de reprodução em Crotalaria mucronata Desv - Cruz de Almeida , Élcio (Revista Ceres, 2025)
In order to elucidate some aspects of the floral biology and reproductive mechanisms of Crotalaria mucronata Desv., some tests like pollen viability and sugar, starch and fat contents in floral whorls were accomplished. Daily visits of insects were also registered.